Improvement of productive efficiency of a production line: a case study in a medical products industry - Amorin, Larissa; Rodrigues, Thales Volpe; Silva Junior, José Ferreira da (Brazilian Journal of Production Engineering, 2020)
Competitiveness in the various industrial segments has encouraged organizations to develop ways to make their operations and production processes more and more efficient and with greater productivity. With this, the companies look for characteristics that allow to have good results in relation to the competition. Thus, this study presents concepts about the application of tools, adequacy of layout and techniques for solving problems, improving the productive efficiency in a production line, ensuring the increase of quality and production by the productivity index and reduction of waste, in a medical products industry. The methodology for the application of process improvement tools was divided into stages, starting with the definition of a theoretical conceptual framework, followed by case planning, pilot testing, data collection, data analysis and reporting. The main results obtained with these changes, we can highlight the reduction of process time by approximately 17%, the improvement in resource allocation, the increase in productivity by approximately 20%. Line balancing also reduced employee idleness, due to the distribution of work activities, without accumulating intermediate stocks and with fewer employees per cell. In addition to improving production availability and reducing unplanned downtime. Thus, the work contributes to the generation of positive results to the process, allowing productivity gains and cost reductions with the optimization of the indicators, allowing the potentializing the results with the continued application of the tools.